Konsep dan Prinsip-Prinsip Manajemen Perspektif Al-Qur’an - Baharudin Ardani; Hamidullah Mahmud (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Administration and management are fundamental concepts in human activity, dating back to creation in Islamic perspective. The Qur'an contains various management principles that emphasize not only efficiency and effectiveness but also the ethical and spiritual values underlying every action. This study aims to explore the concepts of administration and management from the Qur'anic perspective and to apply Qur'anic management principles in everyday life. Using a qualitative-descriptive approach, this research identifies managerial values such as consultation (shura), optimal hard work (itqan), and honesty as guidance for Muslims to achieve a balance between worldly and spiritual goals. In conclusion, Qur'anic-based management not only directs operational success but also yields broad spiritual and social impacts.